1991
DOI: 10.1007/bf01314321
|View full text |Cite
|
Sign up to set email alerts
|

Replication of avian influenza viruses in humans

Abstract: Volunteers inoculated with avian influenza viruses belonging to subtypes currently circulating in humans (H1N1 and H3N2) were largely refractory to infection. However 11 out of 40 volunteers inoculated with the avian subtypes, H4N8, H6N1, and H10N7, shed virus and had mild clinical symptoms: they did not produce a detectable antibody response. This was presumably because virus multiplication was limited and insufficient to stimulate a detectable primary immune response. Avian influenza viruses comprise hemaggl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
173
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(182 citation statements)
references
References 13 publications
7
173
0
2
Order By: Relevance
“…The relative lack of antibody response in our study population, who had substantial exposures to waterfowl with influenza A infections, and in inoculated volunteers from Beare and Webster ( 12 ) suggests that avian influenza infections in humans exposed to wild waterfowl may occur more commonly than we are able to detect with current methods. Although the sample size of our study was relatively small, our results suggest that handling wild waterfowl, especially ducks, is a risk factor for direct transmission of avian influenza virus to humans.…”
Section: Discussionmentioning
confidence: 67%
“…The relative lack of antibody response in our study population, who had substantial exposures to waterfowl with influenza A infections, and in inoculated volunteers from Beare and Webster ( 12 ) suggests that avian influenza infections in humans exposed to wild waterfowl may occur more commonly than we are able to detect with current methods. Although the sample size of our study was relatively small, our results suggest that handling wild waterfowl, especially ducks, is a risk factor for direct transmission of avian influenza virus to humans.…”
Section: Discussionmentioning
confidence: 67%
“…Replication of avian influenza viruses has been observed in experimental human infection, but only when extremely high doses were used. 26 The most favoured hypothesis for the emergence of the pandemic viruses of 1957 and 1968 is that pigs acted as a "mixing vessel" for reassortment between avian and human influenza viruses. 27,28 Studies that identified influenza H3N2 human-avian reassortant viruses in pigs 29 and people 30 in Europe gave support to this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the sporadic isolation of swine viruses from humans (reviewed by Brown (2000)), swine have been postulated to be a "mixing vessel" where avian and mammalian viruses reassort (Scholtissek, 1990). Pigs, unlike humans (Beare and Webster, 1991), seem to be readily infected by avian viruses, and most, if not all, avian hemagglutinin (HA) subtypes are capable of replicating in swine (Kida et al, 1994). The susceptibility of swine to both mammalian and avian viruses is due to the presence of receptors for both lineages of virus in the pig trachea (Ito et al, 1998).…”
Section: Introductionmentioning
confidence: 99%